2010
DOI: 10.1016/j.brainres.2010.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in β-amyloid accumulation in 3xTg-AD mice: Role of neonatal sex steroid hormone exposure

Abstract: The risk of Alzheimer's disease (AD) is higher in women than in men, a sex difference that likely results from the effects of sex steroid hormones. To investigate this relationship, we first compared progression of β-amyloid (Aβ) pathology in male and female triple transgenic (3xTg-AD) mice. We found that female 3xTg-AD mice exhibit significantly greater Aβ burden and larger behavioral deficits than age-matched males. Next, we evaluated how the organizational effects of sex steroid hormones during postnatal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
174
5
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 234 publications
(219 citation statements)
references
References 112 publications
27
174
5
2
Order By: Relevance
“…Consistent with our previous findings [19], immunohistochemical Ab load was more severe in the subiculum of female compared to male 3xTg-AD mice maintained on standard diet (t = 22.2, p,0.05). Significantly increased immunoreactive Ab load was observed in both the hippocampus CA1 (F = 6.51, p,0.02; Figure 5A-E) and the subiculum (F = 5.04, p,0.05; Figure 5F-J) of high fat fed mice in both sexes.…”
Section: Ab Accumulation and Tau Hyperphophorylationsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with our previous findings [19], immunohistochemical Ab load was more severe in the subiculum of female compared to male 3xTg-AD mice maintained on standard diet (t = 22.2, p,0.05). Significantly increased immunoreactive Ab load was observed in both the hippocampus CA1 (F = 6.51, p,0.02; Figure 5A-E) and the subiculum (F = 5.04, p,0.05; Figure 5F-J) of high fat fed mice in both sexes.…”
Section: Ab Accumulation and Tau Hyperphophorylationsupporting
confidence: 92%
“…We have reliably observed a strong correlation between Ab neuropathology and Y-maze SAB impairment in both male and female 3xTg-AD mice [19]. Mice were allowed to explore the Y-maze freely for 5 minutes or until 15 arm choices were made.…”
Section: Behavioral Assessmentmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the expression of genes that showed statistical significance (middle cluster) shows minimal intragroup variance (Figure 4a). The intragroup variability at the top and bottom clusters could be due to a less consistent pathology in male 3xTg‐AD mice (Carroll et al., 2010). To correlate the RNA changes at the protein level, western blot analysis demonstrated that the levels of multiple actin‐binding proteins (including drebrin, spinophilin, and p‐cortactin) were significantly reduced in the 3xTg‐AD mice (Figure 4c,d).…”
Section: Resultsmentioning
confidence: 99%
“…Females were selected because they exhibit significantly greater Aβ burden and larger behavioral deficits than age-matched males. 14 We recently used this model to show that immunotherapy with an anti-Aβ antibody fragment is a potential tool for the treatment of AD. 15 Specifically, we constructed a single-chain variable fragment (scFv), scFv-h3D6, 16 from the humanized monoclonal antibody AAB-001 (mAb-h3D6, bapineuzumab).…”
Section: Introductionmentioning
confidence: 99%